Exploring small-scale sport event tourism in Malaysia - Yusof, Aminuddin; Omar Fauzee, Mohd Sofian; Mohd Shah, Parilah; Soh, Kim Geok (EuroJournals Publishing, Inc., 2009)
The purpose of this study is to explore the potential of a small-scale sport event as tourist attraction in Malaysia using Leiper’s (1990) tourist attraction system as framework. This paper reports the results of a study conducted on a small scale event sport tourism in Lake Kenyir Malaysia. Data for this study were collected quantitatively from 400 subjects using the Leisure Motivation Scale developed by Ragheb and Beard (1983). Data were analyzed using descriptive statistics and logistic regression. Visitors to sport event at Lake Kenyir fall into three categories: (1) sport excursionist, (2) active sport tourist and (3) passive sport tourists and the majority of the respondents (81.75%) were sport tourists. The results indicate factors such as competence mastery and intellectual factors are significant variables which motivate people to seek active sport-oriented vacations. On the other hand, passive sport tourists are motivated by social factors and the need to escape from over stimulating situations. The results were discussed in light of earlier findings concerning sport tourist motivations and preferred destination attributes. The potential and benefits of small scale sport events as tourist attraction in Malaysia were also discussed in this paper as well as suggestions for the local tourism authority.